KOMUNIKASI PEMASARAN MELALUI MEDIA BARU DI SERAMBI BOTANI - Agustina, Lidya (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
This article focused on how to answer the intense of new mediaâs marketing communication strategy in Serambi Botani. The combine of new media marketing communication with conventional marketing communication strategy, which used by Serambi Botani, is the development of the new marketing communication strategy. This study used a qualitative approach and the results show us some facts. First, the consumer of Serambi Botaniâs products is dominated by women. Tthis study also found that there was a change on their consumer behavior, which is on the reach of consumers. Usually, Serambi Botaniâs consumers are local communities, but when Serambi Botani used new media on their marketing communication strategy the reach number of consumers increased to global and local customers. It also has implications to the increased number of product sales. This new consumer behavior can be used as a new marketing communication strategy on Serambi Botani.